Quality of head and neck radiotherapy reporting in randomized controlled trials. Issue 8 (25th March 2018) - Tseng, Michelle; Tan, Teng Hwee; Zheng, Huili; Soon, Yu Yang; Tey, Jeremy
Abstract: Background: The purpose of this clinical review was to determine the quality reporting of radiotherapy (RT) in randomized controlled trials (RCTs) of head and neck cancer and its impact on reporting of the trial primary efficacy and toxicity outcomes. Methods: We searched MEDLINE for eligible RCTs published between 1994 and 2015. We assessed the quality of RT reporting and bias in the reporting of trial outcomes using published criteria. Results: We found 67 eligible trial reports. There was significant variability in the quality of RT treatment reporting among the included trials. Thirty‐two trials had adequate quality RT reporting. Cooperative group trials were more likely to have adequate quality reporting (odds ratio [OR] 3.02; 95% confidence interval [CI] 1.04‐9.85). The quality of RT reporting did not influence the bias in the reporting of trial outcomes. Conclusion: The quality of head and neck RT reporting in RCTs is variable and did not impact on bias in reporting of trial outcomes.